Non-Monotonic Relationship between Human Capital and Unemployment: An Exploratory Study with Empirical Evidence on Singapore - HO, Kong Weng (Institutional Knowledge at Singapore Management University, 2008)
We examine empirically the role of human capital, together with global and domestic technologies, in the evolution of unemployment in Singapore. Our results show a threshold level of human capital, below (above) which increases (decreases) in human capital will reduce (raise) unemployment. This nonmonotonic relationship is caused by a greater substitution from labour toward technology feasible at higher levels of human capital.